Los avatares de la fraternidad: del olvido político a un principio en auge - Liñán García, Ángeles (Estudios eclesiásticos, 2016)
In the academic landscape relevant works have risen up from different geographical and disciplinary framings which insist on the urgent need to rescue and try to implement concepts such as common benefit and reciprocity. Likewise, they aspire to recover in the economic, legal and social sphere the principle of fraternity as a public ideal, which was forgotten, eclipsed or torn apart in today’s society characterized by an exacerbated capitalism and a moral relativism and now it´s the time for it to serve once again as a valid support for the economy and civil society to function properly.